La valoración de la prueba ante la falta de normativa para calificar al testigo como hostil en el Código Orgánico General de Procesos. - Gavilán Cunalata Joffre Rolando (2024)
The means of proof are the tools that are used in a judicial process to demonstrate the truth of the facts proposed by the procedural subjects. They are fundamental in any trial since they provide the judge with the necessary elements of conviction so that the judge forms criteria and can issue his ruling. Within the means of proof we have the testimonial statement, which is the statement made by a witness under oath about the facts that are the subject of the controversy. Once sworn, the witness must answer the questions asked. The figure of the hostile witness is incorporated into the General Organic Code of Processes, in order to punish the little or no cooperation that the witness provides when giving his statement since the witness has the obligation to answer the questions asked of him. formulate Once the witness is declared or hostile, suggestive questions may be asked on introductory topics that do not affect the disputed facts, recapitulate information already provided by the declarant, however, the General Organic Code of Processes does not establish what the procedure is for classify the witness as hostile Keywords: hostile witness, statement, testimonial evidence.